‘Idea-shift’: how ideas from the rest are reshaping global order. - Acharya, Amitav (Third World Quarterly, 2016)
An ‘idea-shift’ is taking place that may be of greater consequence for global governance than is the ongoing ‘power shift’ or the rise of new powers. A number of non-Western thinkers and practitioners - who may be called idea-shifters - have contributed to new concepts and approaches that have radically altered the way we think about development, security and ecology, among other areas. Their ideas are often dismissed or downgraded in the West as imitation, or the product of the Western education of their creators, or of partnership with Western collaborators, governments, donor agencies and multilateral institutions dominated by the Western powers. Challenging this view, this essay holds that ideas from the postcolonial world, its thinkers and policymakers have played an important role in the making of the postwar norms of governance, such as universal sovereignty, human rights, international development and regionalism. Moreover, some of the important recent ideas about development (human development from Mahbub ul Haq and Amartya Sen), security (responsible sovereignty from Francis Deng and colleagues) and ecology (sustainable development from Wangari Maathai) have come from people who, while trained in the West, are deeply influenced by their local context or point of origin. Appreciating how much this local origin and context matters allows us to consider these as ‘ideas-from-below’ and a powerful driver of the unfolding global idea-shift.